Effect of Concentration on the Viscosity of Some Carboxylic Acids in Diluted Aqueous Solutions - Khalaf, Husam S.; AL-Dulaimy, Zainab Abbas; Fendi, Wedad J. (Iraqi Journal of Science, 2024)
In the current study, the effect of concentration on the viscosity of formic acid, acetic acid, and propanoic acid in an aqueous solution is investigated. The apparent molar volume (ϕv) was specified from density measurements at 298.15 K. A restrictive apparent molar volume ϕv˚ under unlimited dilutions of these carboxylic acids has been determined based on Masson's equation. The B and A coefficients for viscosity have been determined using viscosity data for the Jones-Dole equation for all studies, and a positive value of the B-coefficient indicates strong solute-solvent interaction. The modified Jone-Dole equation was projected using a ratio of mole fractions of solute and solvent.